2014
DOI: 10.1016/j.psychres.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the role of psychological inflexibility in Trichotillomania

Abstract: Psychological Inflexibility (PI) is a construct that has gained recent attention as a critical theoretical component of Acceptance and Commitment Therapy (ACT). PI is typically measured by the Acceptance and Action Questionnaire-II (AAQ-II). However, the AAQ-II has shown questionable reliability in clinical populations with specific diagnoses, leading to the creation of content-specific versions of the AAQ-II that show stronger psychometric properties in their target populations. A growing body of literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 52 publications
4
33
0
1
Order By: Relevance
“…Previous research suggests that the degree to which pulling functions to regulate internal experiences is positively related to negative affect (Duke, Keeley, Geffken et al, 2010; Duke, Keeley, & Ricketts, 2010; Shusterman et al, 2009), experiential avoidance (i.e., the tendency to avoid unpleasant, internal experiences via maladaptive practices; Begotka et al, 2004; Houghton et al, 2014), and disorder severity (Begotka et al, 2004; Houghton et al, 2014; Norberg, Wetterneck, Woods, & Conelea, 2007; Shusterman et al, 2009). Consequently, we hypothesized that the “internal-regulated pulling” subscale would be positively related to anxiety, depression, experiential avoidance, and TTM severity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research suggests that the degree to which pulling functions to regulate internal experiences is positively related to negative affect (Duke, Keeley, Geffken et al, 2010; Duke, Keeley, & Ricketts, 2010; Shusterman et al, 2009), experiential avoidance (i.e., the tendency to avoid unpleasant, internal experiences via maladaptive practices; Begotka et al, 2004; Houghton et al, 2014), and disorder severity (Begotka et al, 2004; Houghton et al, 2014; Norberg, Wetterneck, Woods, & Conelea, 2007; Shusterman et al, 2009). Consequently, we hypothesized that the “internal-regulated pulling” subscale would be positively related to anxiety, depression, experiential avoidance, and TTM severity.…”
Section: Resultsmentioning
confidence: 99%
“…The Acceptance and Action Questionnaire- Trichotillomania (AAQ-TTM; Houghton et al, 2014) is a nine-item self-report measure of experiential avoidance (also referred to as psychological inflexibility) specific to TTM. Items are rated on a 1 (“never true”) to 7 (“always true”) scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TTM research has predominantly treated anxiety as a unidimensional construct (e.g., Diefenbach, Mouton-Odum, & Stanley, 2002; Diefenbach, Tolin, Hannan, Crocetto, & Worhunsky, 2005; Diefenbach, Tolin, Meunier, & Worhunsky, 2008; Duke, Bodzin, Tavers, Geffken, & Storch, 2009; Houghton et al, 2014; Shusterman, Feld, Baer, & Keuthen, 2009; Stanley et al, 1994). However, anxiety researchers recognize anxiety as a multidimensional construct consisting of cognitive (sometimes referred to as subjective anxiety; e.g., fear and worry) and somatic (e.g., physiological arousal and panic) dimensions (Clark & Watson, 1991; Nitschke, Heller, Imig, McDonald, & Miller, 2001; Ree, French, MacLeod, & Locke, 2008).…”
mentioning
confidence: 99%
“…To this end, a growing body of research focuses on the role of psychological inflexibility (i.e., one’s propensity to prioritize the mitigation of undesirable private experiences over the continuation of adaptive goal pursuits; Bond et al, 2011). For example, studies have found that psychological inflexibility mediates the relationship between hair pulling severity and both unidimensional measures of anxiety (Houghton et al, 2014) as well as some of the cognitive aspects of anxiety (i.e., apprehension/anxious thoughts about being negatively evaluated by others; Norberg et al, 2007). However, it is unclear whether psychological inflexibility mediates the relationship between TTM severity and the broader cognitive anxiety dimension.…”
mentioning
confidence: 99%